Eye Tracking and Immersive Environments: Analysing the Automotive Experience - Miguez, Rafael; Brito, Gabriel de; Leão, Felipe; Winkler, Ingrid (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2024.244738, 2024)
This study combines virtual reality and eye tracking to provide insights about a drivers’ attention and perception. The study follows the Design Science Research paradigm, in which we are using Unreal Engine and PICO 4 Enterprise VR head-mounted display to develop a prototype of a virtual vehicle in an immersive environment, allowing for the analysis of eye-tracking data. Our preliminary results demonstrate that eye tracking is effective in creating heat maps, aiding in the identification of focal points and distractions. Our research contributes to enhance usability testing, user experience, and safety within the automotive industry.